QOL-32. ENABLING ACCESS TO SUPPORT; WHAT CAN WE LEARN FROM THOSE THAT DO AND DO NOT ATTEND PARENT SUPPORT GROUPS?. Issue 2 (22nd June 2018) - Thomas, Sophie; Bennett, Emily; Talbot, Emily; Lee, Abigail; Thomas, Shirley
Abstract: Parents in Mind is a six-session evening support and information group designed for parents of childhood brain tumour survivors at Nottingham Children's Hospital UK. Further to successful evaluation it is soon to be rolled out to other regional UK centres and translated to other patient groups. We will present aspects of our evaluation of Parents in Mind conducted via questionnaires and qualitative interviews. We will focus on findings that inform reflections on how we can improve access for families in need of support. In particular we will present the factors participants report as helpful or unhelpful in enabling their attendance. We will combine these with obstacles to attendance as identified via feedback from those families who did not or were unable to attend to identify the most important factors likely to enable and predict attendance. It is often observed that those who do not attend are the most vulnerable families who are particularly in need of support, and thus we intend to promote discussion on how future support services can be designed to maximise attendance and inclusion of vulnerable families.